2016
DOI: 10.1080/09638288.2016.1217072
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of barriers to inclusion in the European workplace

Abstract: This snapshot suggests there is still a gap between intent and reality in workplace inclusion and further strategies are needed to improve the opportunities for employees with disabilities. The paper argues that ergonomics may have a key role to play in tackling these challenges and adapting the workplace environment and job design to suit the needs of individual employees. Implications for rehabilitation This study suggests there is considerable scope for workplace adaptation and improvements to meet the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 2 publications
0
9
0
4
Order By: Relevance
“…[14] For many employers, this creates a dilemma between fulfilling the requirements of reasonable accommodation for persons with mental disabilities on the one hand and ensuring productivity and profit on the other [15]. A multi-country exploratory survey in Europe revealed the willingness of employers to improve inclusion in the workplace and their need for specialist assistance to provide accommodation in the workplace for persons with mental disabilities [16]. However, a review by Khalema and Shankar suggested that globally, the majority of employers are unwilling to employ persons with severe mental illness on account of their perceived poor work ability [17].…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…[14] For many employers, this creates a dilemma between fulfilling the requirements of reasonable accommodation for persons with mental disabilities on the one hand and ensuring productivity and profit on the other [15]. A multi-country exploratory survey in Europe revealed the willingness of employers to improve inclusion in the workplace and their need for specialist assistance to provide accommodation in the workplace for persons with mental disabilities [16]. However, a review by Khalema and Shankar suggested that globally, the majority of employers are unwilling to employ persons with severe mental illness on account of their perceived poor work ability [17].…”
Section: Research Papermentioning
confidence: 99%
“…In all these processes, the cooperation and acceptance of the employer and information for employers about mental disabilities were shown to be significant for the successful inclusion of persons with mental disabilities in the workplace [20,21]. However, studies showed that employers would employ only those they deemed fit [16,22,23]. Although quota systems for employing persons with disabilities have been used to boost employment in high-income countries, their usefulness appears limited in low-and middle-income countries due to weak legislative implementation and a predominantly informal workforce [12,24].…”
Section: Research Papermentioning
confidence: 99%
“…Nevertheless, alongside the anti-discrimination legislation, many EU countries continue to operate the quota system that puts employers of a certain size and in both the private and public sectors, under a strict obligation to employ a fixed percentage of PwDs. Compliance, however, remains relatively low (Fuchs, 2014;Moody et al, 2016;OECD, 2003). Instead, the 'reasonable accommodation duty' introduced by anti-discrimination legislation does not specify or limit the range of accommodations (Balser, 2007) and is believed to ensure PwDs equal access to mainstream employment (Hvinden, 2013;Schur et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, these conflicts resemble conflicts from work narratives (Moody et al, 2017). Arlie Hochschild's now classic study Time Bind (1997), for instance, maps how 'work becomes home and home becomes work'.…”
Section: Discussionmentioning
confidence: 99%